The Right to Asylum and the Principle of Non- Refoulement Under the European Convention on Human Rights - Ristik, Jelena (European Scientific Journal, ESJ, 2017)
The European Convention on Human Rights does not contain any explicit reference to the right to asylum. However, the European Court of Human Rights has provided protection of asylum seekers mainly through interpretation of Article 3 of the Convention. Moreover, even if there is no specific mention of non-refoulement in this Article, the Court has interpreted it to include the prohibition of refoulement. Today, the ECHR is one of the most important juridical instruments for protection of asylum seekers throughout Europe. The main reason for this is that the principle of nonrefoulement under the Convention extends to inhuman and degrading behavior. This paper has placed its focus on the applicability of the ECHR to asylum cases, particularly the development and treatment of the principle of non-refoulement, as a form of complementary protection to those seeking asylum. This will be elaborated mainly through analysis of the jurisprudence of the ECtHR. It will be shown that the principle of non-refoulement under the ECHR, as a barrier to removal, plays a significant complementary role regarding the protection of asylum seekers. It will also be shown that the jurisprudence of the ECtHR has important relevance to EU asylum law and policy. In this sense, a comparison between EU law and ECHR protection standards for asylum seekers will be elaborated as well. Finally, it will be concluded that EU Member States are faced with dual systems providing protection to asylum seekers, and a possible solution will be suggested in order to overcome this situation.